Characteristics of gut microbiota and fecal metabolomes in patients with celiac disease in Northwest China - Shi, Tian; Feng, Yan; Liu, Weidong; Liu, Huan; Li, Ting; Wang, Man; Li, Ziqiong; Lu, Jiajie; Abudurexiti, Adilai; Maimaitireyimu, Ayinuer; Hu, Jiali; Gao, Feng (Frontiers in Microbiology, 2022)
Celiac disease (CD) is an autoimmune small bowel disease. The pattern of gut microbiota is closely related to dietary habits, genetic background, and geographical factors. There is a lack of research on CD-related gut microbiota in China. This study aimed to use 16S rDNA sequencing and metabolomics to analyze the fecal microbial composition and metabolome characteristics in patients diagnosed with CD in Northwest China, and to screen potential biomarkers that could be used for its diagnosis. A significant difference in the gut microbiota composition was observed between the CD and healthy controls groups. At the genus level, the abundance of Streptococcus, Lactobacillus, Veillonella, and Allisonella communities in the CD group were increased (Q<0.05). Furthermore, the abundance of Ruminococcus, Faecalibacterium, Blautia, Gemmiger, and Anaerostipes community in this group were decreased (Q<0.05). A total of 222 different fecal metabolites were identified in the two groups, suggesting that CD patients have a one-carbon metabolism defect. Four species of bacteria and six metabolites were selected as potential biomarkers using a random forest model. Correlation analysis showed that changes in the gut microbiota were significantly correlated with changes in fecal metabolite levels. In conclusion, the patterns of distribution of gut microbiota and metabolomics in patients with CD in Northwest China were found to be unique to these individuals. This has opened up a new way to explore potential beneficial effects of supplementing specific nutrients and potential diagnostic and therapeutic targets in the future.